Central stars of galactic planetary nebulae: New spectral classifications and catalogue - Weidmann, Walter Alfredo (2010)
Context: There are more than 3000 confirmed and probable known Galactic planetary nebulae (PNe), but central star spectroscopic information is available for only 13% of them. Aims: We undertook a spectroscopic survey of central stars of PNe at low resolution and compiled a large list of central stars for which information was dispersed in the literature. Methods: We observed 45 PNs using the 2.15 m telescope at Casleo, Argentina. Results: We present a catalogue of 492 confirmed and probable CSPN and provide a preliminary spectral classification for 45 central star of PNe. This revises previous values of the proportion of CSPN with atmospheres poor in hydrogen in at least 30% of cases and provide statistical information that allows us to infer the origin of H-poor stars.